INISIASI KRISTEN: : SEJARAH, TAHAPAN, PERAYAAN DAN TEOLOGI - Rahawarin, Bernard A. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
In this article we want to reflect on the ritual or procedure which is practised by any cultural entity or religious assembly towards those who want to join this respective cultural group or religious denomination. This so-called “initiation” follows a certein procedure or ritual by which the candidate receives a new status. In order to become a member of the Roman Catholic Church, the candidate must submit himself to a process of initiation, which is meant to be a period of introduction and investigation on whether the candidate fulfills certein conditions. This initiation is aimed to provide to the aspirant full membership of the Church as a community of faithful. By means of this christian initiation the candidate is received as some one who believes in Christ. Faith is to be the orientasion and target in the process of christian initiation.